Copper‐Catalyzed Direct Oxidative α‐Alkoxylation of 4‐Isochromanones. Issue 17 (5th May 2021) - Wu, Xiang; Song, Shuang‐Gui; Zhang, Xin; Fu, Yan‐Ming; Zhu, Cheng‐Feng; Li, You‐Gui
Abstract: The direct oxidative α‐alkoxylation of carbonyl compounds is very important, highly desirable but relatively rare. A general and convenient approach has been developed to prepare 3‐oxy‐4‐isochromanones by copper‐catalyzed α‐C(sp 3 )−H alkoxylation of 4‐isochromanones with alcohols. The key features are easily available starting materials, mild reaction conditions, broad substrate scope, and excellent regioselectivity. Abstract : A general and convenient approach to prepare 3‐oxy‐4‐isochromanones has been developed by copper‐catalyzed α‐C(sp 3 )−H alkoxylation of 4‐isochromanones with alcohols. The key features are easily available starting materials, mild reaction conditions, broad substrate scope, and excellent regioselectivity.